Surface properties of diamond-like amorphous carbon - Kelires, Pantelis C. (My University, 1998)
Monte Carlo simulations show that the surface in tetrahedral amorphous carbon networks reconstructs in a graphite-like manner. The top surface layer is found to be largely composed of distorted sixfold-ring patterns of sp2 sites. Stresses at the surface are tensile, while they vary with depth in a complex oscillatory way. Defect formation energies close to the surface are much less than in the crystal.
Keywords: Carbon; Monte Carlo method; Computer simulation